A promising lead-free fluoride carbonate SHG material designed from a theoretical perspective. Issue 8 (6th February 2017) - Hu, Jinyu; Ma, Zuju; Sa, Rongjian; Zhang, Yongfan; Wu, Kechen
Abstract : The structure–property relationships of a new lead-free fluoride carbonate SHG material were systematically studied using first-principles calculations. Abstract : In recent years, a series of fluoride carbonate crystals, as second harmonic generation (SHG) materials, have been considerably developed; however the lead in these materials is a potential threat to the environment. In this study, the structure, mechanical and optical properties of ABCO3 F (A = Rb, Cs; B = Ge, Sn) were systematically investigated to find alternatives to APbCO3 F. We found that the RbSnCO3 F crystal displays substantial stability and remarkable linear optical properties compared with those of the lead fluoride carbonate SHG materials. In particular, RbSnCO3 F exhibits unexpected anisotropy of refractive indices, a key feature to satisfy the phase matching condition in the ultraviolet spectral region. In addition, RbSnCO3 F shows a large SHG response, about 21 times that of KH2 PO4 (KDP) with the coefficient of 8.21 pm V −1 . Our results highlight that RbSnCO3 F should be a candidate for a lead-free fluoride carbonate SHG material for achieving coherent light output in laser fields. This investigation also unravels the structure–property relationship of fluoride carbonates, contributing to explore more excellent SHG materials in future.